2019
DOI: 10.1002/aenm.201803238
|View full text |Cite
|
Sign up to set email alerts
|

Biomass‐Derived 3D Carbon Aerogel with Carbon Shell‐Confined Binary Metallic Nanoparticles in CNTs as an Efficient Electrocatalyst for Microfluidic Direct Ethylene Glycol Fuel Cells

Abstract: as biological renewability, low toxicity, and easy storability. [5] Despite the recent improvements in DEGFCs, the technology is still hindered by the problems of conventional platinum (Pt) anode catalysts, such as surface poisoning, high cost, and scarcity. [6] Recently, palladium (Pd) nanostructures have emerged as a promising EG oxidation catalyst in alkaline media, eliminating the necessity of the Pt nanocatalyst for EG oxidation. [7] However, Pd nanocatalysts are prone to rapid deterioration under surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(46 citation statements)
references
References 77 publications
1
42
0
Order By: Relevance
“…In the last few decades, various nanomaterials (e. g., noble metals, alloy metals, transition metal compounds) were applied to construct enzyme‐free glucose sensors. Recently, transition metal oxides, transition metal hydroxides and transition metal sulfides have been prevalently used as non‐noble‐metal catalysts for glucose electro‐oxidation, originating from its good electrocatalytic activity, low cost and abundant source.…”
Section: Introductionmentioning
confidence: 78%
“…In the last few decades, various nanomaterials (e. g., noble metals, alloy metals, transition metal compounds) were applied to construct enzyme‐free glucose sensors. Recently, transition metal oxides, transition metal hydroxides and transition metal sulfides have been prevalently used as non‐noble‐metal catalysts for glucose electro‐oxidation, originating from its good electrocatalytic activity, low cost and abundant source.…”
Section: Introductionmentioning
confidence: 78%
“…For smaller Co:Ni ratios, presence of Co decreased NP size. N and S doped PdNi/CA was prepared by adding raw cotton into palladium(II) chloride and nickel(II) acetate solution (Raj kumar et al, 2019). After hydrothermal treatment with thiourea, PdNi anchored carbon fiber hydrogels doped with N and S were obtained.…”
Section: Sol-gel Routementioning
confidence: 99%
“…Supported Pd electrocatalysts also suffered from rapid degradation and poisoning (Li et al, 2016). N and S doped PdNi/CA NPs confined in carbon nanotubes (CNT) were tested for ethylene glycol oxidation by cyclic voltammetry (CV) in alkaline electrolyte and in a microfluidic direct ethylene glycol fuel cell (Raj kumar et al, 2019). Authors reported that CNT growth increased the flexibility of CA and the carbon shell around the PdNi NPs prevented agglomeration, delamination, and dissolution, hence increasing the stability.…”
Section: Applications Catalysismentioning
confidence: 99%
“…Fuel cells are clean, efficient, and promising technology for the future . Fuel cells are available of different types such as proton exchange membrane fuel cells, direct methanol fuel cells, direct ethanol fuel cells, alkaline fuel cells, direct formic acid fuel cells, direct urea fuel cells, direct ethylene glycol fuel cells, and direct glucose fuel cells . Glucose is the valuable carbohydrate in nature and could be readily extracted from biomass.…”
Section: Introductionmentioning
confidence: 99%